Dependence of Antimicrobial Effects of Guanidine-containing Pectin Derivatives from Some Structural Characteristics - O. R. Akhmedov; S. A. Shomurotov; A. S. Turaev; A. V. Sidarenka (Разработка и регистрация лекарственных средств)
Introduction. Up to the present time, there are practically no studies on the relationship between the structural characteristics and biological activity of antimicrobial polymers synthesized by the chemical addition of guanidine groups to polysaccharide macromolecules. Therefore, there is a need to carry out the chemical modification of guanidine with natural polymers, in particular polyaldehyde pectin, and to conduct comparative studies of the antimicrobial activity of the obtained samples with different physicochemical characteristics.Aim. To conduct the synthesis of guanidine-containing pectin derivatives. In addition, to determine the influence of structural variations in the obtained samples on exhibiting antimicrobial properties.Materials and methods. The synthesis of guanidine-containing pectin derivatives consisted of the following stages: periodate oxidation of the polysaccharide, modification of guanidine using polyaldehyde pectin, and chemical reduction of azomethine bonds. The amount of guanidine in the obtained samples was calculated by acidimetric titration, the nitrogen content (N, %) was determined using a Eura EA (Italy) elemental analyzer. The рКα values of the synthesized compounds were found by the back titration method. Absorption spectra were analyzed on a "UV 1280" spectrophotometer (Shimadzu, Japan) in the range λ = 180–400 nm. IR spectra were recorded on a Vector-22 spectrometer in the wavelength range of 400–4000 cm-1 in KBr tablets (3 mg sample / 300 mg KBr). The molecular weight characteristics of the synthesized derivatives were determined by high-performance gel permeation chromatography on an Agilent 1260 Infiniti liquid chromatograph. The acute toxicity of guanidine-containing pectin derivatives was calculated by the Prozorovsky method. Comparative assessment of antimicrobial activity was conducted by agar diffusion method.Results and discussion. By varying the oxidation level of polyaldehyde pectin, synthesized compounds differ in the degree of substitution, guanidine content, molecular weight, and pKα value. It was found that the levels of the antibacterial and antifungal activity of the studied samples depend on the degree of substitution and the nature of the counterion. The antimicrobial effect increases with an increase in the quantitative content of guanidine groups in the macromolecular chain of pectin. Moreover, it was found that the change of low molecular weight Cl–, NO3– , F–, I– counterions by carboxylate anions leads to a sharp decrease in antimicrobial properties. Upon oral injection of the synthesized compounds to mice, it was found that all samples belong to the category of practically non-toxic substances (V-class).Conclusion. Comparative analysis of guanidine-containing pectin derivatives with different characteristics showed that the severity of the antimicrobial action of the synthesized compounds against bacteria and fungi of the genus Candida depends on the quantitative content of cationic groups and the nature of the counterion.